Variasi Musiman Ketebalan Lapisan Termoklin di Perairan Barat Sumatra: Thermocline Layer Thickness in the Waters off the Western Coast of Sumatra - Zulfatur Rohmah Zulfa; Irkhos; Suhendra; Lizalidiawati (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2025)
The oceanographic dynamics of the western waters of Sumatra can be observed through the characteristics of the thermocline layer. Information on thermocline thickness is essential for understanding seasonal variations over the past decade. This study aims to identify the seasonal variability in thermocline thickness along the coastal and offshore regions of western Sumatra by analyzing six observation points representing both zones. A quantitative and descriptive approach was employed, utilizing monthly average vertical temperature data from 2010 to 2019, obtained from the Marine Copernicus database. Data processing was conducted using Panoply software and Microsoft Excel 2010, producing seasonal average thermocline thickness values and time series graphs. The results show that the highest thermocline thickness was recorded at 130.3 meters in the coastal area of Bengkulu during the first transitional season, and 138.7 meters in the offshore area of Lampung during the southeast monsoon. In contrast, the lowest thermocline thickness was observed during the northwest monsoon, reaching 74.9 meters from the coast to offshore regions of Bengkulu and Lampung, as well as in the coastal to offshore areas of Aceh in August. The increased thermocline thickness during the first transitional season in Bengkulu to Lampung waters is attributed to the distribution of surface winds transporting warm water masses along the western coast of Sumatra. Meanwhile, the thinner thermocline layer observed during the southeast monsoon suggests the occurrence of upwelling in the region.